Electrochemical investigation of amorphous silica-based anode materials for lithium batteries - Cunanan, Maricris C.; Cervera, Rinlee Butch M. (Quezon City College of Engineering, University of the Philippines Diliman, 2016)
Lithium-ion battery technology is promising for energy storage to support the intermittent renewable energy sources. Since the 1980s, commercially available LIBs generally use graphitic carbon as their anode material. Attention has since shifted to Si-based Li alloys to deliver a higher anode capacity at values of 4,200 mAhg-1. However, the large volumetric change of bulk Si during cycling results to a shorter cycle life and fast capacity fading. Nanostructuring has thus been eyed as one viable strategy to improve capacity retention. In this study, amorphous nanosilica was obtained from (1) rice hull (RH) waste through acid precipitation and from (2) TEOS via a low-temperature sol-gel method, doped with 5mol percent and 10mol percent Fe and subsequently calcined at two settings: 400 degree celsius for 1h and 800 degree celsius for 2h. The microstructural properties of all the samples were fully investigated. TG-DTA showed a total weight loss of 89 percent for pure dried RH and a total weight loss of 19 percent for pre-calcined pure SiO2 from TEOS. XRD patterns of RH-sourced samples revealed a combination of amorphous and crystalline peaks. On the other hand the 5 percent - and 10 percent -doped TEOS-sourced samples calcined at 400 degree celsius were purely amorphous while those calcined at 800 degree celsius contained both amorphous and crystalline SiO2 peaks. The SEM micrographs obtained suggest that a higher Fe content and higher calcination temperature promoted grain growth and created particle agglomeration. EDS analysis, meanwhile, confirmed the complete removal of carbon residues and the incorporation of Fe into the SiO2 matrix. FTIR results showed the three characteristic absorption bands arising from Si-O-Si groups. Based on the PSA metrics computed, the particle of the TEOS-sourced samples were moderately dispersed as opposed to the broadly dispersed particles of the RH-sourced samples. From the electrochemical performance of the samples with 0.05 mA current with Li as the anode, the best working electrode in terms of specific capacities and Coulombic efficiencies are 5 percent 800 RH and 10 percent 800 RH, respectively. The former had a lithiation and delithiation capacity of 959.52 mAhg-1 and 238.58 mAhg-1, and a 24.86 percent CE. The 10 percent 800 RH, meanwhile, attained a lithiation and delithiation capacity of 787.47 mAhg-1 and 203.47 mAhg-1, and a 25.84 percent CE.
Thesis (M.S. Materials Science and Engineering)--University of the Philippines Diliman
Keywords: Lithium ion batteries; Lithium cells; Rice hulls -- Silica content; Anodes